Innovation of Baznas Rural Microfinance: Economic Stability Solutions in the Middle of the Covid-19 Pandemic - Nurma Khusna Khanifa; Kurniawati Mutmainah; Achmad Affandi (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2022)
Since the beginning of 2020, precisely in March, Indonesia was shocked by one of the phenomena, namely the Covid-19 pandemic. The deployment and an increasing number of Covid-19 cases occurred rapidly with a tremendous impact (extraordinary) on health, humanitarian, financial system stability and the reduction of the Indonesian economy. At that time, Indonesia experienced a difficult situation. Moreover, the difficulties were faced by the people of Indonesia. Both the state and the people need financial support. One of the largest financial sources in Indonesia, other than taxes, is zakat. Then, effective zakat empowerment needs to be done, especially during the Covid-19 pandemic. In the era of the Covid-19 pandemic, such a breakthrough needs to be made by zakat management institutions by looking at the situation and condition of the community. Zakat needs to be managed by a credible institution, such as BAZNAS. BAZNAS is an Islamic philanthropic institution dedicated to empowering the poor with a cultural approach through philanthropic activities (compassion/affection) and prophetic social entrepreneurship. To support this, innovations from zakat management institutions are needed so that the distribution is right on target to people in need. One of the innovations owned by BAZNAS is BAZNAS Rural Microfinance. BAZNAS Rural Microfinance is a program that utilizes zakat for productive businesses for people who are classified as weak (mustahiq) and have a commitment to entrepreneurship. This breakthrough in mustahiq empowerment is one of the programs that aim to meet the basic needs of people affected by Covid-19.